Association between gravidity and risk of metabolic syndrome: Results of Tabari cohort study. Issue 5 (September 2020) - Moosazadeh, Mahmood; Takezaki, Toshiro; Saeedi, Majid; Kheradmand, Motahareh
Abstract: Background and aims: The purpose of the present study was to investigate the association of gravidity and age at first pregnancy with metabolic syndrome in a large-scale, population-based cohort study in Iran. Methods: The present secondary analysis was conducted on a subset of the population (5739 women with at least one pregnancy) enrolled in the Tabari cohort study. Reproductive history was collected using a structured questionnaire. The relationship of gravidity and age at first pregnancy with metabolic syndrome and its components was analyzed using the logistic regression model. Results: The results showed that after adjustment for confounding variables, the odds of having metabolic syndrome was not significantly associated with age at first pregnancy (P = 0.269) and gravidity (P = 0.504). However, there was an association between hypertension and age at first pregnancy (OR = 0.32, 95% CI = 0.12–0.82; P = 0.03). Additionally, waist circumference was also associated with gravidity (OR = 2.17, 95% CI = 1.37–3.35). Conclusion: As the findings indicated, age at first pregnancy and gravidity were not associated with the odds of having metabolic syndrome. However, a relationship was found between first pregnancy at the age of >35 years and the decreased risk of hypertension. Gravidity was also found to be a dose-dependent risk factor for increased waist circumference. Highlights: We report a population based retrospective study of 5739 women and determined relationship between gravidity and metabolic syndrome. Age at first pregnancy and gravidity was not associated with the odd of having metabolic syndrome. Waist circumference was positively associated with the gravidity, and hypertension was positively associated with age at first pregnancy.